Implanting Ni-O-VOx sites into Cu-doped Ni for low-overpotential alkaline hydrogen evolution - Yibing Li (Nature Portfolio, 2020)
Producing H2 from water using electricity and earth-abundant elements is necessary for worldwide renewable fuel production, yet most electrocatalysts have sluggish activities or poor stabilities. Here, authors show vanadium oxide modified copper-doped nickel to enable active and durable H2 evolution.